2016
DOI: 10.1007/s11832-016-0713-0
|View full text |Cite
|
Sign up to set email alerts
|

EOS® biplanar X-ray imaging: Concept, developments, benefits, and limitations

Abstract: PurposeIn 1992, Georges Charpak invented a new type of X-ray detector, which in turn led to the development of the EOS® 2D/3D imaging system. This system takes simultaneous anteroposterior and lateral 2D images of the whole body and can be utilized to perform 3D reconstruction based on statistical models. The purpose of this review is to present the state of the art for this EOS® imaging technique, to report recent developments and advances in the technique, and to stress its benefits while also noting its lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
136
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(151 citation statements)
references
References 73 publications
1
136
0
3
Order By: Relevance
“…To our knowledge, the MDSS X-ray imaging system is currently not used for diagnostic X-ray examinations, as comprehensive studies to determine whether this system can be used for other anatomical regions have not been undertaken. There is an indication that the MDSS imaging system has a potential for use as a conventional radiographic imaging system 13 . It has also been shown that the image quality of the MDSS imaging system is comparable to that of conventional DR imaging systems for the clinical spine protocol 14 .…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the MDSS X-ray imaging system is currently not used for diagnostic X-ray examinations, as comprehensive studies to determine whether this system can be used for other anatomical regions have not been undertaken. There is an indication that the MDSS imaging system has a potential for use as a conventional radiographic imaging system 13 . It has also been shown that the image quality of the MDSS imaging system is comparable to that of conventional DR imaging systems for the clinical spine protocol 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The EOS low-dose imaging system (EOS imaging®, Paris, France) has been developed to produce high quality images at low radiation doses 6 . We have been using the EOS scanner for full-spine examinations at our institution, since the fall of 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Such differences between previous studies have been suggested to be partly due to the difficulty in standardizing these patients' positioning during X-ray acquisition (Kelley and Wedge, 2013), especially in the presence of hip rotation. In this study, the use of biplanar X-rays with three-dimensional reconstruction for the assessment of hip anatomy, which has been previously shown to decrease the effect of patient positioning bias (Melhem et al, 2016), should have allowed precise evaluation of the anatomy of the Down syndrome hip.…”
Section: Discussionmentioning
confidence: 99%